2019
DOI: 10.1093/biolinnean/blz074
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity of wild rabbit populations: implications for archaeology and palaeontology

Abstract: Morphometric characteristics of the European rabbit (Oryctolagus cuniculus) are regularly used in archaeological and palaeontological studies to explore aspects of prehistoric human hunting behaviour, to reconstruct past environments or to define new species. However, the variability of these characteristics is still both poorly understood and under-documented due to a lack of population-level data that are essential for reliably interpreting the fossil record of this species. Here we address the morphometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In many mammals, the size and shape of skeletal and dental elements can be both influenced by intrinsic and extrinsic factors (Scott 1987 ; Kappelman 1988 ; DeGusta and Vrba 2005 ; Eronen et al 2006 ; Klein et al 2010 ; Polly 2010 ; Meachen et al 2016 ; Ledevin et al 2016 ; Renaud et al 2018 ; Pelletier 2018 , 2019 ; Souquet et al 2019 ). It has been shown that some of these parameters, such as geographic position, topography or marked variations in climate and the environment, could also notably influence the body size and/or morphology of reindeer (Thomas and Everson 1981 ; Collins and Smith 1991 ; Weinstock 1997 , 2002 ; Weladji and Holand 2003 , 2006 ; Weladji et al 2003 ; Reimers et al 2005 ; Mårell et al 2006 ; Magniez 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…In many mammals, the size and shape of skeletal and dental elements can be both influenced by intrinsic and extrinsic factors (Scott 1987 ; Kappelman 1988 ; DeGusta and Vrba 2005 ; Eronen et al 2006 ; Klein et al 2010 ; Polly 2010 ; Meachen et al 2016 ; Ledevin et al 2016 ; Renaud et al 2018 ; Pelletier 2018 , 2019 ; Souquet et al 2019 ). It has been shown that some of these parameters, such as geographic position, topography or marked variations in climate and the environment, could also notably influence the body size and/or morphology of reindeer (Thomas and Everson 1981 ; Collins and Smith 1991 ; Weinstock 1997 , 2002 ; Weladji and Holand 2003 , 2006 ; Weladji et al 2003 ; Reimers et al 2005 ; Mårell et al 2006 ; Magniez 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…1996; Callou 2003; Davis & Moreno‐García 2007; Pelletier et al . 2015 a , b ; Pelletier 2018, 2019; Davis 2019), the vast majority of palaeontological works is based on the study of shape variations of the third lower premolar (p3). This tooth is widely used to distinguish leporid species and to reveal their phylogenetic relationships (Petter 1959, 1961; Hibbard 1963; López‐Martínez et al .…”
Section: Figmentioning
confidence: 99%
“…2000; De Marfà & Mein 2007; De Marfà 2008, 2009; Angelone & Rook 2012; Angelone 2013; Pelletier et al . 2015 a , b ; Pelletier 2018, 2019). However, the relevance of these dental criteria could be revised in relation to the data acquired on modern individuals.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations